Biochemical characteristics of tea from amaranth leaves (Amaranthus cruentus L.) of the ‘Frant’ variety - D. V. Sokolova; A. E. Solovyeva (Пищевые системы)
Tea and various tea beverages have always been popular products rich in antioxidants. Amaranth is considered a “super product” due to the content of high-quality gluten-free protein, unsaturated fatty acids, vitamins and minerals. The leaves of the red-colored varieties of Amaranthus cruentus L., rich in amaranthine, are an excellent raw material for the production of tea beverages. The purpose of this study was comparative investigation of the biochemical composition and antioxidant activity of tea from amaranth leaves of the ‘Frant’ variety prepared both with and without fermentation. For the first time, the content of valuable biochemical substances in a tea drink made from amaranth has been established: ascorbic acid, chlorophylls, carotenoids and lutein, which are strong antioxidants and necessary for human health. The composition of tea has a high content of chlorophylls (540.14–567.65 mg/100g), carotenoids (116.62–127.64 mg/100g), and amaranthine (44.61– 54.18 mg/100g). During fermentation, there was a significant increase in ascorbic acid, lutein and total acidity. Analysis of the content of low-molecular-weight components of the carbohydrate profile showed a significant decrease of sucrose, raffinose and monosaccharide altrose and an increase in glucose and ribose. The composition of the acids included 28 compounds with a predominance of inorganic phosphoric acid and organic acids: succinic and glyceric. It has been established that during the fermentation process accompanied by an increase in total acidity, the carbohydrate content decreases, which leads to a decrease in the sweet taste of tea. Factors associated with the antioxidant activity of amaranth tea were identified. The benefit of amaranth tea is confirmed by the significant presence of quercetin, ferulic and ellagic acids. The identified correlations are of theoretical and practical importance for understanding the processes occurring during the fermentation of amaranth leaves.